The influence of maturity on recovery and perceived exertion, and its relationship with illnesses and non-contact injuries in young soccer players - Mandorino, Mauro; J. Figueiredo, António; Condello, Giancarlo; Tessitore, Antonio (Biology of Sport, 2022)
A high training load could increase the risk of injury in soccer players. However, there is still a lack of knowledge regarding the effect on young athletes, in whom a different maturity status could lead to different physiological responses to training. Therefore, the aim of this study was to investigate the association of internal load markers and recovery status with risk of illnesses and non-contact injuries in young soccer players characterised by different maturity status. Twenty-three U14 soccer players were monitored during a full season and categorised according to years from peak height velocity (PHV). Based on the estimated values, athletes were divided into three different groups: Pre-PHV, Circa-PHV and Post-PHV players. The following internal load markers were monitored: rating of perceived exertion (RPE), session rating of perceived exertion (S-RPE), weekly load (WL), cumulative loads for 2, 3, and 4 weeks (WL2, WL3, WL4), acute to chronic workload ratio for 2, 3 and 4 weeks (A:C2, A:C3, A:C4) and week-to-week percentage variation (%WL). Recovery status was quantified using the total quality recovery (TQR) scale. Z-score transformation was adopted for TQR and RPE values and the difference between the parameters was calculated (Z-TQR-RPE). The Kruskal-Wallis test was adopted to evaluate differences in TQR and RPE with respect to maturity offset. A multinomial regression analysis was performed to evaluate the association between internal load markers and risk of illness and non-contact injuries. The variables that showed a significant association were included in the receiver operating characteristic (ROC) curve analysis. The results revealed that RPE was significantly higher (p < 0.01) and TQR significantly lower (p < 0.05) in Post-PHV compared to Pre- and Circa-PHV. Moreover, RPE, A:C4, TQR and Z-TQR-RPE showed a significant (p < 0.01) association with non-contact injuries. The internal load markers included in ROC curve analysis showed poor predictive ability (AUC ≤ 0.6). A rapid increase in training load together with a decrease in recovery status may produce higher susceptibility to illnesses and non-contact injuries. The contrasting physiological responses found in relation to maturity status could explain the different injury predisposition in young soccer players.